2005
DOI: 10.1093/schbul/sbj012
|View full text |Cite
|
Sign up to set email alerts
|

Reviews: Emerging Empirical Evidence on the Ethics of Schizophrenia Research

Abstract: Many challenging ethical questions come with the scientific efforts to understand the nature and treatment of schizophrenia. The empirical study of ethical aspects of schizophrenia research has sought to clarify and resolve many of these questions. In this article we provide an overview of the existing data-based literature on schizophrenia research ethics and outline directions for future inquiry. We examine 5 broad categories of inquiry into the ethics of schizophrenia research: (1) Scientific designs (eg, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 219 publications
(278 reference statements)
0
73
0
Order By: Relevance
“…The final version included 4 items for examining understanding, 5 for appreciation, and 1 for reasoning. We chose not to assess the expression of choice because this aspect is usually not impaired in most neuropsychiatric populations 7,8 and a deficit in this area tends to be obvious during the consent process without a specific formal evaluation. We have previously found that persons with schizophrenia have greater difficulty with openended questions than with those requiring answers of the yes or no type.…”
Section: Item Generation and Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final version included 4 items for examining understanding, 5 for appreciation, and 1 for reasoning. We chose not to assess the expression of choice because this aspect is usually not impaired in most neuropsychiatric populations 7,8 and a deficit in this area tends to be obvious during the consent process without a specific formal evaluation. We have previously found that persons with schizophrenia have greater difficulty with openended questions than with those requiring answers of the yes or no type.…”
Section: Item Generation and Selectionmentioning
confidence: 99%
“…[16][17][18][19][20] In terms of divergent validity, UBACC scores should not be strongly associated with severity of positive symptoms. 8,[18][19][20] …”
Section: Validity Analysesmentioning
confidence: 99%
“…Furthermore, awareness that people often decide quickly about participating in research could lead to a greater awareness by researchers and research policymakers of the need for safeguards beyond the requirement of signed informed consent-an argument we and others have made elsewhere (Appelbaum, 1996;Dunn, Candilis, & Roberts, 2006;Dunn & Gordon, 2005;Moreno, Caplan, & Wolpe, 1998;Roberts, 1998;Roberts, Hammond, Warner, & Lewis, 2004;Shore, 2006;Verheggen, Nieman, & Jonkers, 1998). It is thus encouraging that our straightforward and brief educational intervention shows promise in promoting awareness and attitudes among medical professionals.…”
Section: Shaping Medical Students' Attitudesmentioning
confidence: 94%
“…Embedded within this concept is the importance of regard for the autonomy, dignity, and unique strengths and vulnerabilities of each individual who participates in the research endeavor (National Commission for the Protection of Human Subjects of Biomedical and Behavioral Research, 1979). Honoring the full meaning of this ethical principle in clinical research involves affirming the rights and safeguarding the well-being of clinical research volunteers, and it also entails understanding participants' personal values, motivations, and experiences (Dunn & Roberts, 2005;Dunn, Candilis, & Roberts, 2006;Roberts & Roberts, 1999).…”
mentioning
confidence: 99%
“…A comprehensive review of the ethics of schizophrenia research has recently been published in the literature (Dunn et al 2006). …”
Section: Special Concerns Regarding Psychiatric Patientsmentioning
confidence: 99%